Influence of elevated temperatures up to 100 °C on the mechanical properties of concrete - Acosta Urrea, Fernando (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2018)
Experiments to characterize the effects of moisture content and temperature on the mechanical properties of concrete were conducted. Based on these experiments, a new overall material model capable of predicting the mechanical behaviour of concrete subject to elevated temperatures up to 100 °C was developed. The material model estimates the time, temperature and moisture dependency of the compressive and tensile strength, creep and shrinkage of concrete.